2016
DOI: 10.2147/copd.s123315
|View full text |Cite
|
Sign up to set email alerts
|

Drop in lung function during asthma and COPD exacerbations – can it be assessed without spirometry?

Abstract: BackgroundWhen assessing patients with exacerbation of asthma or COPD, it may be useful to know the drop in forced expiratory volume in 1 second (FEV1) compared with stable state, in particular when considering treatment with oral corticosteroids. The objective of the study was to identify indicators of drop in FEV1 during exacerbations.MethodsIn this prospective multicenter study from primary care, patients diagnosed with asthma or COPD were examined at stable state and during exacerbations the following year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…However, when they occur early during inspiration, the clinician has reason to suspect COPD, and even more so when heard bilaterally, although such crackles may also indicate bronchiectasis 23 and asthma. 17 The PPVs found in our study are similar to those found for high COPD questionnaire scores 24 25 But, identification of crackles cannot match the questionnaires in terms of sensitivity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, when they occur early during inspiration, the clinician has reason to suspect COPD, and even more so when heard bilaterally, although such crackles may also indicate bronchiectasis 23 and asthma. 17 The PPVs found in our study are similar to those found for high COPD questionnaire scores 24 25 But, identification of crackles cannot match the questionnaires in terms of sensitivity.…”
Section: Discussionsupporting
confidence: 62%
“…We examined a sample of the general population who were mainly in a stable clinical state, and only a few of those with COPD were examined during an exacerbation. In patients with COPD, the prevalence of crackles tend to increase during exacerbations, 17 and a stronger association between crackles and COPD would probably be found if patients with COPD with exacerbations had been a particular focus of this study. Visualising spectrograms during the classification might have been of additional help in assessing the timing and type of crackles.…”
Section: Discussionmentioning
confidence: 89%
“… 26 However, crackles are commonly heard in COPD, 27 and especially during exacerbations, related to worsened bronchial obstruction. 28 In the present study, while the link between crackles and antibiotic prescribing was independent of CRP result, a greater number of participants in the high CRP group (59.2%) experienced crackles than did those in the low CRP group (44.0%), indicative of a relationship between crackles and more seriously unwell participants. Further investigation is required to determine the diagnostic and prognostic value of crackles and other chest sounds, and whether further safe reductions in antibiotic prescribing for AECOPD are possible.…”
Section: Discussioncontrasting
confidence: 44%
“…Although the impact of acute exacerbations on pulmonary function measurements has been well described [11][12][13], their impact on CT lung density has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%